Islamic Marketing Values and Their Impact on Sales Volume: Insights from Wahyu Jaya Store, Banda Aceh - Fakhruddin (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2024)
Principles are based on the ethical, moral and spiritual values ​​adhered to by Muslims. Applying these principles in marketing strategies can help companies attract Muslim customers who are more aware of these values. The purpose of this research is to determine the Islamic marketing principles applied in an effort to increase sales volume and determine the impact of implementing Islamic marketing principles at Wahyu Jaya Store, Banda Aceh City. This research uses a qualitative method with a descriptive approach. Research data was collected by interviewing the owner, store head, employees and customers at Wahyu Jaya Store. The results of this research explain that the Wahyu Jaya Store really upholds Islamic values ​​in marketing, such as upholding the values ​​of justice and honesty, paying attention to moral values, paying attention to the benefits and satisfaction of consumers or customers, continuing to provide the best service to consumers, providing superior quality, carrying out alms and social good deeds, not being wasteful and saving money, transparency in transactions, and continuing to carry out new and creative innovations. It is hoped that we will continue to apply Islamic marketing principles more and more so that we can continue to develop our business and not deviate from the teachings that Rasulullah SAW taught us. And also in order to optimize the management and business development carried out by Wahyu Jaya Store. Wahyu Jaya Store in marketing not only applies sharia marketing principles but also applies modern principles that do not deviate from the teachings of the Islamic religion. Applying these principles will certainly really help Wahyu Jaya Store in increasing sales volume with evidence that many customers have returned to shop at Wahyu Jaya Store and have become regulars. Wahyu Jaya Store not only pays attention to success in the world, but pays attention to and desires success in the world and the hereafter or what is called Al-Falah.